Pemanfaatan bio-char sebagai pembawa mikroba untuk pemantap agregat tanah Ultisol dari Taman Bogo-Lampung The use of bio-char as bacterial carrier for aggregate stabilization in Ultisol Soil from Taman Bogo-Lampung - Laksmita Prima SANTI; Didiek Hadjar GOENADI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2010)
Abstract A series of research was carried out with the objective to meet the challenge and determine the direction and strategy required for overcoming highly weathered Ultisol soil that impact to low productivity. Selected ameliorating materials, i.e. bio-char, compost, and peat were examined their physical characteristics to determine the best combination of them as bioameliorant carrier materials for aggregate stability bacteria. Bio-char was found to be the most suitable carrier material as it has highest total pore spaces and available water content. Microbial population obtained from the granular forms of bioameliorant was 107 CFU/gram of the sample until 12 months life time periods. Best vegetative growth performance of maize Bisma var. in Ultisol soil of Experiment Station (KP) Taman Bogo was shown by the application of 100% standard dosage of NPK conventional fertilizers in combination with the addition of 4.2 g/plant of bioameliorant. Yield of dry grain of maize was higher (+15.7 %) by application of 100 % standard dosage and 2.1g bioameliorant/plant (112 kg/ha) than that obtained by standard dosage of conventional fertilizer. Abstrak Satu rangkaian kegiatan penelitian telah dilakukan untuk menjawab tantangan, arah dan strategi dari berbagai aspek yang terkait erat dengan masalah pelapukan lanjut dan berdampak pada rendahnya produktivitas tanah Ultisol. Beberapa bahan terpilih seperti arang pirolisis (bio-char), kompos, dan gambut dianalisis secara fisik untuk menetapkan kombinasi terbaik sebagai bahan pembawa bioamelioran dengan bahan aktif bakteri pemantap agregat. Bio-char memiliki keunggulan dalam hal total ruang pori dan kapasitas air tersedia yang lebih tinggi. Sampai dengan 12 bulan masa simpan, populasi bakteri pada bioamelioran granul dengan bahan pembawa bio-char berjumlah 107 CFU/gram contoh. Pertumbuhan terbaik tanaman jagung varietas Bisma pada tanah Ultisol diperoleh dari perlakuan 100 % pupuk NPK tunggal yang dikombinasikan dengan 4,2 g bioamelioran/tanaman. Sementara itu, perlakuan 100 % dosis pupuk NPK tunggal yang dikombinasikan dengan 2,1 g bioamelioran/tanaman (112 kg/ha) menghasilkan bobot pipilan kering jagung yang lebih tinggi (+15,7 %) apabila dibandingkan dengan perlakuan 100% dosis pupuk NPK tunggal saja.